Produktivitas Tebu (Saccharum officinarum L.) Asal Bibit Bud Chips (Ujung, Tengah, Pangkal) Akibat Aplikasi Mulsa Bagasse - Nalendra Andeva; Wiwik Indrawati; Any Kusumastuti (Jurnal Agro Industri Perkebunan, 2018)
The use of bud chip seeds in meeting the needs of quality seeds in an effort to increase the production and yield of sugar cane. The use of bagasse will be a source of nutrients for plants, so that the optimum cane growth and increase sugar cane production. The objective of this study was to obtain the highest yield between bud chip position, bagasse mulch dose, and to know the interaction between bud chip budding treatment with bagasse mulch treatment on sugar cane rendement.. This research was conducted in teaching farm of Politeknik Negeri Lampung from June 2016 until February 2017. The experiments were performed using Randomized Block Design (RBD) in factorial pattern consisting of two factors. The first factor is the position of bud chips consisting of 3 levels i.e. top, middle, and base. The second factor is bagasse mulch dosage consisting of 4 levels i.e. 0 ton.ha-1, 3 ton.ha-1, 6 ton.ha-1, and 9 ton.ha-1. The result of this research showed that the position of bud chips on the top stem has an effect on the number of stem and the productivity of sugarcane compared to the midle and base stem position. The position of bud chips treatment result showed no effect on the yield of sugarcane. The dose of bagasse 3 ton.ha-1, 6 ton.ha-1, and 9 ton.ha-1 showed no effect on the stem diameter, the number of stem, and the rendement of sugarcane, but affected by the dose mulch of bagasse 0 ton. ha-1. The dose of bagasse 3 ton.ha-1 showed the best effect on the number of stem per row and the productivity of sugarcane compared to all bagasse mulch treatments. There was no interaction between the treatment of sugarcane bud chips and mulch bagasse on all observation variables.Â Keywords: bud chips, bagasse mulch, sugarcane yield